Pre-transplant Thymic Function Predicts Is Associated With Patient Death After Kidney Transplantation - Courivaud, Cécile; Bamoulid, Jamal; Crepin, Thomas; Gaiffe, Emilie; Laheurte, Caroline; Saas, Philippe; Ducloux, Didier (Frontiers in Immunology, 2020)
Accelerated thymic involution is a main feature of end-stage renal disease (ESRD)-associated immune senescence. Recent evidences suggest that ESRD-associated immune senescence is associated with adverse outcomes in dialysis patients. However, no study focused on the association between pre-transplant thymic function and patient survival after transplantation. We conducted a prospective, multicenter study to assess whether pre-transplant thymic function measured by recent thymic emigrants (RTE) may predict death after first kidney transplantation. Results were tested in a validation cohort. 967 incident kidney transplant recipients were included in the prospective study. Mean follow up was 5.1+2.9 years. 82 patients (8.5%) died during follow up. Lower RTE levels were associated with a higher risk of death (2.53; 95%CI, 1.54 to 4.39 for each decrease of 1 log in RTE; p<0.001). Cancer-related death was particularly increased in patients with low RTE levels (4.23; 95%CI, 1.43 to 12.13; p=0.007). 136 patients having received a first kidney transplantation were included in the validation cohort. Lower TREC levels were associated with higher risk of death (1.90; 95%CI, 1.11 to 3.51 for each decrease of 1 log in RTE; p=0.025). RTE were not associated with death-censored graft loss. Pre-transplant thymic function is strongly associated with death after transplantation. Attempt to reverse ESRD-related thymic loss may prevent premature death.